Os processos de retextualização e de construção de sentidos em audiências cíveis de instrução e julgamento - Barreiros, Alda da Silva (Universidade do Vale do Rio dos Sinos, 2019)
The current paper, named The Processes of Retextualization and meaning constructions in Civil evidentiary and judgment hearing, aims to investigate the oral and written texts as communicative and meaning production events inside the language discursive actions, from the Interface of Conversation Analysis and Textual Linguistics with Law. Such focus is coated with a special importance in legal and language universe, since there is a formal conversation in an institutional context in an evidentiary and judgment hearing, mainly turned to oral proof, which is, as a rule, turned into written text, for later exam and valuation by the judge at the time of the judicial sentence. In this context, the goal of this research is to analyse the processes of retextualization construction of referentials that occur while moving from oral to written, which is, from witness hearing to a written register of the testimony that integrates the judicial process. It is a qualitative and case study, based in two research fields: Conversation analysis (MARCUSCHI,1999), of textual- interactive perspective, and Textual linguistics, especifically with retextualization and reference notions (JUBRAN, 1992, 2006; KOCK, 1998. 2002, 2006, 2008, 2015, 2017; MARCUSCHI,2001, 2008, 2010; MONDADA, DUBOIS, 2003, 2015). The research corpus is formed by three transcriptions recorded in audio of witnesses testimonies, taken by State Judiciary Branch. The analysis of this corpus allowed ascertainment that the retextualization used by the judge results in a considerable linguistics and informational reduction on the written version of the testimonies, which is also the most formal one. Although the anaphoric and deictics coreferential recoveries are frequent in written and spoken texts, it’s in the testimonial making, a product of the speech, where a bigger number and variety of referential strategies are identified, which shows different ways of meaning constructions when we move from the tipically oral text in case to the written retextualized text, the testimonial making term. Thus, it’s possible to observe that retextualization performed by the judge, in witness hearing situation in civil audience of instruction and judgement, considerably influences the written register of testimonies through erasure of the processes of construction of speech objects and of many referential strategies in written text, which depends, greatly, on “the judge interpretative decisions”. (ALVES, 1992).
Keywords: Audiência; Depoimento; Testemunha; Retextualização; Referenciação; Hearing; Testimony; Witness; Retextualization; Referencing; ACCNPQ::Lingüística, Letras e Artes::Lingüística